Vapor Permeation of Aqueous Ethanol through Agarose-Sericin Membrane - Okada, Kazunari; Yoshikawa, Masakazu (Journal of Membrane and Separation Technology, 2015)
A self-standing membrane was obtained from renewable polymers, such as agarose and sericin. Differential scanning calorimetric study revealed that there were two states of water in the membrane, such as bound water and free water. The membrane preferentially transported water from aqueous ethanol mixture by vapor permeation. Preliminary study revealed that the present membrane was applicable to forward osmosis.